PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT ACTIVITY OF THE HYDROETHANOLIC EXTRACT OF Passiflora edulis f. flavicarpa RESIDUES - de Oliveira, Jussimara Barros; das Neves, Jorge Vitório Gomes; da Silva, Marcondes Viana (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2016)
Most fruit residues are known for being rich in bioactive phytochemicals such as polyphenols (natural antioxidants), responsible for major health benefits when consumed regularly due to their role in the prevention of degenerative diseases. The objective of this study was to determine the phytochemical composition (condensed tannins, total flavonoids, and total phenolic content) and evaluate the antioxidant capacity (DPPH and ABTS assays) of the flour prepared from yellow passion fruit residues, composed of epicarp and mesocarp, generated by fruit pulp processing industries. Passion fruit residues were subjected to heat treatment in an oven with renewal and air circulation and processed into flour. The phytochemical composition results revealed the following: condensed tannins, 0.31 mg.100g-1; total flavonoids, 23.87 mg.100g-1; and total phenolic content, 24.87 mg.100g-1. The DPPH assay showed that the yellow passion fruit residue flour has significant antioxidant activity, and there was a positive correlation between antioxidant activity and the total phenolic content according to the ABTS assay and the DPPH radical scavenging method. Passion fruit residue flour is a source of natural antioxidants with potential to be used in the food industry as an ingredient in the development of food products with functional claims.